Effects of kinesio taping on static balance performance and muscle activity in children with developmental coordination disorder: a single-group pretest-posttest study - Li-Liang Li; Fu-Chen Chen (Medical Journals Sweden, 2023)
Objective: To compare the effects of various kinesio tape applications on static balance and muscle activity in children with developmental coordination disorder.  Methods: Four taping conditions were applied to 48 children with developmental coordination disorder: no taping, gastrocnemius taping, tibialis anterior taping; and peroneus longus taping. Postural sway and electromyographic data were assessed, with eyes closed (30 s), standing still in 2-leg stance, dominant-leg stance, and non-dominant-leg stance. Results: Kinesio taping significantly reduced postural sway in both anteroposterior and mediolateral directions for dominant-leg stance and non-dominant-leg stance, but not 2-leg stance. During single-leg stances, anteroposterior sway was significantly lower for the gastrocnemius taping condition than for the no taping, tibialis anterior and peroneus longus taping conditions, and significantly lower in the tibialis anterior and peroneus longus taping conditions than in the no taping condition (gastrocnemius < tibialis anterior = peroneus longus < no taping). In addition, mediolateral sway was significantly lower in the tibialis anterior and peroneus longus taping conditions than in the no taping and gastrocnemius taping conditions, and significantly lower in the gastrocnemius taping condition than in the no taping condition (tibialis anterior = peroneus longus < gastrocnemius < no taping). Electromyographic data showed that muscle activity was significantly greater only for muscles where kinesio tape was applied. Conclusion: Various kinesio tape applications can differentially reduce postural sway and increase muscle activity during single-leg stances in children with developmental coordination disorder.